Nrf2 and regulation of the antioxidant system in the Antarctic silverfish, Pleuragramma antarctica: adaptation to environmental changes of pro-oxidant pressure - Giuliani, Maria Elisa; Benedetti, Maura; NIGRO, MARCO; Regoli, Francesco (Marine Environmental Research, 2017)
Despite the key importance of Nrf2-Keap1 in regulating antioxidant system in vertebrates, this system is still poorly investigated in marine species. The present study focused on the Antarctic silverfish Pleuragramma antarctica which, during the final phases of embryo development in platelet ice, is challenged by a sudden enhancement of environmental oxidative conditions associated to ice melting. Partial coding sequences were identified for Nrf2, it repressor Keap1 and for typical Nrf2-target antioxidant genes, like catalase, glutathione peroxidase isoform 1 and Cu/Zn-dependent superoxide dismutase. Compared to temperate homologues, the protein sequences showed an elevated conservation of amino acids essential for catalytic functions, while a few specific substitutions in non-essential regions may represent a molecular adaptation to improve flexibility and accessibility to active site at cold temperatures. The role of the Nrf2-Keap1 pathway in modulating the activation of antioxidant defences at both transcriptional and functional levels with a clear temporal increase of antioxidant protection in embryos before the hatching. Such findings confirm the importance of Nrf2 and highlight regulation of antioxidants as an adaptive strategy and in P. antarctica to protect the early life stages toward the environmental changes of pro-oxidant pressure.